Selective Ion Penetration of Graphene Oxide Membranes - Sun, Pengzhan; Zhu, Miao; Wang, Kunlin; Zhong, Minlin; Wei, Jinquan; Wu, Dehai; Xu, Zhiping; Zhu, Hongwei (ACS nano, 2013)
The selective ion penetration and water purification properties of freestanding graphene oxide (GO) membranes are demonstrated. Sodium salts permeated through GO membranes quickly, whereas heavy-metal salts infiltrated much more slowly. Interestingly, copper salts were entirely blocked by GO membranes, and organic contaminants also did not infiltrate. The mechanism of the selective ion-penetration properties of the GO membranes is discussed. The nanocapillaries formed within the membranes were responsible for the permeation of metal ions, whereas the coordination between heavy-metal ions with the GO membranes restricted the passage of the ions. Finally, the penetration processes of hybrid aqueous solutions were investigated; the results revealed that sodium salts can be separated effectively from copper salts and organic contaminants. The presented results demonstrate the potential applications of GO in areas such as barrier separation and water purification.